(untitled) (Conference Series, 2022)
The foundation of Indonesia is Pancasila that allows 6 religions in our country to live together in society. Therefore, it is a country with a high religious pluralism level, yet the churches nowadays are being exclusive in the society. Christians as a minority tend to be distant with the society members around them. While the principles in Christianity are actually encouraging Christians to be able to be inclusive in society. This research has the purpose to show the importance of the churches being inclusive. The method used is a qualitative method with a literature study approach. The focus of the research is on the application of the principles of Christianity that are not against the Christian faith and Pancasila to be applied practically in the midst of religious pluralist society. The result of the research shows that Christianity could be exclusive in the matter of faith and inclusive in life application. The teaching of Christian faith definitely is not against the basic values of the Indonesian ideology, that is Pancasila.